Primary Percutaneous Coronary Intervention in Patients With Type 2 Diabetes With Late/Very Late Stent Thrombosis and de novo Lesions: A Single-Center Observational Cohort Study of Clinical Outcomes and Influencing Factors - Zhao, Xiaoxiao; Lan, Jun; Yu, Xiaoping; Zhou, Jinying; Tan, Yu; Sheng, Zhaoxue; Li, Jiannan; Wang, Ying; Chen, Runzhen; Liu, Chen; Zhou, Peng; Chen, Yi; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: This study compared differences in the risk factors and clinical outcomes of primary percutaneous coronary intervention (PCI) in type 2 diabetes mellitus (DM) and non-DM patients with de novo lesions (DNLs) and late or very late stent thrombosis (LST/VLST). Methods: We used angiography to screen 4,151 patients with acute coronary syndrome for DNL and LST/VLST lesions. Overall, 3,941 patients were included in the analysis and were allocated to the DM (n = 1,286) or non-DM (n = 2,665) group at admission. The primary endpoint was a composite of major adverse cardiovascular events (MACEs), defined as death, myocardial infarction, revascularization, and ischemic stroke, within a median follow-up period of 698 days. Results: In the group with a total white blood cell count >10 × 109/L (P = 0.004), a neutral granular cell count >7 × 109/L (P = 0.030), and neutrophil–lymphocyte ratio >1.5 (P = 0.041), revascularization was better for DNL than for LST/VLST lesions. Among DM patients with DNLs, each unit increase in age was associated with a 53.6% increase in the risk of MACEs [hazard ratio (HR): 1.536, 95% confidence interval (CI), 1.300–1.815, P < 0.0001]. Older age (≥65 years) was associated with a significantly greater risk of MACEs (P < 0.0001). Furthermore, each standard deviation (SD) increase in the level of peak white blood cell counts was associated with a 50.1% increase in the risk of MACEs (HR, 1.501; 95% CI, 1.208–1.864; P = 0.0002). When stratifying the DM population with DNLs according to the D-dimer baseline and peak levels <0.5 vs. ≥0.5 mg/L, the high D-dimer group at baseline had a 2.066-fold higher risk of MACEs (P < 0.0001), and the high peak level D-dimer group had a 1.877-fold higher risk of MACEs (P = 0.001) compared to the low-level groups. Among DM patients with LST/VLST, each unit increase in age was associated with a 75.9% increase in the risk of MACEs (HR: 1.759, 95% CI, 1.052–2.940, P = 0.032). Furthermore, for each SD increase in the peak D-dimer level, the risk of MACEs increased by 59.7% (HR, 1.597; 95% CI, 1.110–2.295; P = 0.041). Conclusion: Following successful primary PCI, the measurement of baseline and peak D-dimer values may help identify individuals at high cardiovascular risk. This suggests a potential benefit of lowering D-dimer levels among T2DM patients with DNL. Furthermore, age and the peak D-dimer values may facilitate the risk stratification of T2DM patients with LST/VLST.